2008
DOI: 10.1159/000151676
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Fetal Supraventricular Tachycardia and Obstetric Cholestasis

Abstract: Objective: Supraventricular tachycardia (SVT) is the most common form of sustained fetal tachyarrhythmia in pregnancy. The development of hydrops with SVT is associated with significant worsening of prognosis. Case: We report a case of fetal SVT with hydrops at 28 weeks’ gestation that required both transplacental and direct fetal treatment in a woman with concurrent obstetric cholestasis. Antiarrhythmic therapy and control of the maternal liver function and bile acid levels with ursodeoxycholic acid was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…Bile acids have been shown to cause cardiac arrhythmias in an in vitro model of the fetal heart, and this effect is ameliorated by the addition of UDCA to the culture medium . Although human data are lacking, there are three case reports of antenatal fetal cardiac arrhythmia in the literature, including drug‐resistant supraventricular tachycardia (SVT), refractory SVT and atrial flutter . It should be noted that the outcome in all three of these pregnancies was good.…”
Section: Associated Adverse Perinatal Outcomesmentioning
confidence: 99%
“…Bile acids have been shown to cause cardiac arrhythmias in an in vitro model of the fetal heart, and this effect is ameliorated by the addition of UDCA to the culture medium . Although human data are lacking, there are three case reports of antenatal fetal cardiac arrhythmia in the literature, including drug‐resistant supraventricular tachycardia (SVT), refractory SVT and atrial flutter . It should be noted that the outcome in all three of these pregnancies was good.…”
Section: Associated Adverse Perinatal Outcomesmentioning
confidence: 99%
“…A few studies have reported abnormal fetal heart rates (≤ 100 or ≥ 180 beats per minute (bpm)) as well as reduced heart rate variability in ICP (Gorelik et al, 2003;Inizi et al, 2006;Laatikainen, 1975;Reid et al, 1976;Shand et al, 2008). Therefore, spontaneous beating rate was assessed in neonatal rat cardiomyocytes cultured with fibroblasts.…”
Section: Counteracting the Effect Of Taurocholic Acidmentioning
confidence: 99%
“…Fetal tachycardia and bradycardia have been reported in ICP [7,18]. More recently, there have been reports of fetal atrial flutter and supraventricular tachycardia in ICP pregnancies [19,20]. …”
Section: Bile Acid Signaling and The Fetal Heartmentioning
confidence: 99%